2014
DOI: 10.5551/jat.23374
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Autologous Bone Marrow Mononuclear Cell Therapy in Patients with Peripheral Arterial Disease

Abstract: Aim: Peripheral arterial disease (PAD), particularly critical limb ischemia (CLI), is a severe cause of amputation and mortality. More than 50% of diabetic patients with CLI die within four to five years. The development of novel stem cell therapies may bring new hope to these patients. We aimed to assess the efficacy of autologous bone marrow cell therapy for treating CLI using a meta-analysis. Methods: We searched the literature in PubMed, the Cochrane Central Registry of Controlled Trials, the Elsevier data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…The administration of BM‐MNCs, PB‐MNCs and BM‐MSCs in diabetic CLI patients has resulted in significant improvements in limb perfusion and ulcer healing rates, reductions in amputation rates, and angiographic analysis has demonstrated significant new vessel and collateral circulation formation . These results are consistent with those of meta‐analyses of studies in CLI patients where diabetic patients comprised a significant percentage . Although results so far seem promising, large placebo‐controlled RCT are still needed.…”
Section: Peripheral Artery Disease In the Diabetic Footmentioning
confidence: 99%
“…The administration of BM‐MNCs, PB‐MNCs and BM‐MSCs in diabetic CLI patients has resulted in significant improvements in limb perfusion and ulcer healing rates, reductions in amputation rates, and angiographic analysis has demonstrated significant new vessel and collateral circulation formation . These results are consistent with those of meta‐analyses of studies in CLI patients where diabetic patients comprised a significant percentage . Although results so far seem promising, large placebo‐controlled RCT are still needed.…”
Section: Peripheral Artery Disease In the Diabetic Footmentioning
confidence: 99%
“…Benoit et al (2011), evaluated randomized controlled trials involving bone marrow derived stem and progenitor cells (n=295) and found that the amputation rates between the control arms and treatment arms was statistically significant (25.4% vs.14.8% p=0.02) demonstrating that bone marrow derived cells do improve outcomes in CLI patients [23]. Furthermore, Wang et al analysed 31 published Randomized Controlled Trials (RCTs) and non-RCTs, having a total of 1,214 patients, and advantageous effects of autologous bone-marrow cell therapy was reported, where majority of severe adverse events (SAEs) were associated with hospitalization for disease process-related complications and not related to cell therapy [24]. Ponemone et al evaluated the safety and therapeutic effectiveness of intra-muscular injections of a BMC in 17 no-option CLI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell transplantation was established to induce promotion of repair of ischemic tissue partially through angiogenesis which has been shown in models of hind limb ischemia for example [1]. Stem cell therapies differ with respect to the origin of the cells, cell numbers and route of application [2][3][4][5]. Studies were for example performed with unfractionated bone marrow cells, endothelial progenitor cells and/or peripheral blood mononuclear cells which make comparison very difficult [3][4][5].…”
Section: Introductionmentioning
confidence: 99%